2023
DOI: 10.1021/acsomega.2c07377
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adsorption and Evaluation of Tetracycline Removal in an Aquatic System by Modified Silica Nanotubes

Abstract: In the present study, a nanocomposite adsorbent based on mesoporous silica nanotubes (MSNTs) loaded with 3aminopropyltriethoxysilane (3-APTES@MSNTs) was synthesized. The nanocomposite was employed as an effective adsorbent for the adsorption of tetracycline (TC) antibiotics from aqueous media. It has an 848.80 mg/g maximal TC adsorption capability. The structure and properties of 3-APTES@MSNT nanoadsorbent were detected by TEM, XRD, SEM, FTIR, and N 2 adsorption− desorption isotherms. The later analysis sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 195 publications
1
5
0
Order By: Relevance
“…3 showed that the rate of removal was higher in the beginning due to the presence of larger adsorbent surface area which indicated that there were more numerous binding sites to which the indigo dye can be attached. Similar observation was reported in [16]. After maximum adsorption was reached, the rate of dye uptake was reduced; this showed that the potency of all these adsorbents reduced after the maximum contact time was reached.…”
Section: Effect Of Contact Time and Kinetic Modellingsupporting
confidence: 88%
See 1 more Smart Citation
“…3 showed that the rate of removal was higher in the beginning due to the presence of larger adsorbent surface area which indicated that there were more numerous binding sites to which the indigo dye can be attached. Similar observation was reported in [16]. After maximum adsorption was reached, the rate of dye uptake was reduced; this showed that the potency of all these adsorbents reduced after the maximum contact time was reached.…”
Section: Effect Of Contact Time and Kinetic Modellingsupporting
confidence: 88%
“…To investigate the kinetics of adsorption of Indigo blue on the kernel fibers, the rate constants were determined in terms of the pseudo-first-order equation, pseudosecond-order equation and intra-particle diffusion equation. The pseudo-first-order equation describes the kinetics of adsorption process as represented in Equation 2 [16].…”
Section: Adsorption Kinetic Modellingmentioning
confidence: 99%
“…Increasing ionic strength promotes Doxo.HCL self-association, potentially aiding in adsorption. 69 According to a zeta (ζ) potential study, adjusting pH to a neutral level might also enhance the adsorption process, possibly through intermolecular connections and screening of positively charged Doxo.HCL molecules. 69 Additionally, other parameters, such as π−π stacking interactions, play a role in adsorbing pollutants, as reported in a previous study.…”
Section: Effect Of Concentrationmentioning
confidence: 99%
“…69 According to a zeta (ζ) potential study, adjusting pH to a neutral level might also enhance the adsorption process, possibly through intermolecular connections and screening of positively charged Doxo.HCL molecules. 69 Additionally, other parameters, such as π−π stacking interactions, play a role in adsorbing pollutants, as reported in a previous study. 68 Interestingly, the pH of the medium has little impact on Doxo.HCL adsorption, suggesting that π−π stacking interactions are another significant mechanism contributing to pollutant removal.…”
Section: Effect Of Concentrationmentioning
confidence: 99%
“…14 In addition, MOFs are crystalline solids. 15 Furthermore, MOFs based on polyhedral coordination cages are attracting a lot of attention, not just because of their aesthetic appeal but also because the restricted cavities that they provide (i) can be used as a molecular flask to enclose visitor species in a protective shell to prevent chemical reaction, (ii) it is possible to separate and store gases using them, and (iii) it is possible that they will have magnetic and catalytic properties that are uncommon. Based on flexible and porous shape, MOFs' guest ions and molecules, with such metals, can infiltrate into the wholesale material, whereas this guest ions or molecules can be selectively adsorbed due to the shape and size of the pores.…”
Section: Introductionmentioning
confidence: 99%